Theoretical and experimental study of gas-phase corrosion attack of Fe under simulated municipal solid waste combustion: Influence of KCl, SO2, HCl, and H2O vapour. (1st August 2019) - Chen, Guanyi; Wenga, Terrence; Ma, Wenchao; Lin, Fawei
Highlights: A gas-Fe surface reaction kinetic mechanism was developed. Corrosion behaviour of pure Fe metal was simulated and experimentally investigated. Different concentrations of KCl, SO2, H2 O, and HCl were tested for corrosion of Fe. 10 vol% H2 O and 300–500 ppm SO2 were the concentrations for lowest corrosion rate. Abstract: Combustion of municipal solid waste (MSW) in waste-to-energy plants have an advantage of energy recovery. However, corrosion of super-heaters induced by KCl, H2 O, and S in MSW is the major problem limiting the efficient utilisation of MSW. Corrosion reactions of metals are not well understood at molecular/atomic levels, regarding how they evolve. This situation emphasizes the need to understand the reaction pathways and their reaction rates in order to identify operating conditions that reduces the corrosion rates. In this study, a novel kinetic model for the gas-surface reactions of KCl, S, and H2 O with Fe was developed. The rate constants for the elementary reactions were estimated based on density functional theory and conventional transition state theory computations. Fe-clusters (Fen, n = 2–4) were used in estimating the kinetic constants of the surface reactions. Reaction model was used to predict the corrosion behaviour of Fe in simulated flue-gas of combustion of MSW at 500 °C and 4 bars. A perfectly stirred reactor code of chemkin-PRO was employed for the predictions. Due to the novel nature of the mechanism, independent experimental results from the literature and experimental results from well-controlled conditions at 500 °C and 4 bars for 50 h were used to validate model predictions. Comparison of model predictions and all experimental results showed good agreement. The concentration of KCl accelerated the corrosion of Fe by a parabolic behaviour while SO2 between 300–500 ppm showed the lowest mass loss. Water vapour of ∼10 vol% was the critical point at which above corrosion rate was accelerated.